Contemporary Algerian Poetry in Academic Studies: Insights from Mohamed Arous's Thesis - Fatiha Lagder; Saliha Sebgag (The Journal of Studies in Language, Culture and Society, 2024)
This research paper examines the current state of contemporary Algerian academic critical studies. It explores contemporary Algerian poetry through modern critical mechanisms and approaches to uncover its aesthetic values. The selected study for analysis concentrates on semantic density and suggestive capacity arising from the overlap of various literary genres, the use of symbols, intertextuality, myth, and other experimental mechanisms employed by contemporary poets, who are noted for challenging the conventions of direct declarative poetry. The paper assesses whether these academic studies are analytical, semiotic, stylistic, or a combination of different critical approaches. It specifically monitors the reception of contemporary Algerian poetic discourse, with a particular focus on doctoral theses due to their scientific significance and their role as a pinnacle in the academic study process. Doctoral theses also represent a critical core in the field of academic criticism. The descriptive-analytical approach was utilized to analyze the academic study, applying mechanisms of criticism of criticism. This approach involves summarizing the content of the thesis, "The Overlap of Literary Genres in Contemporary Algerian Poetry: Its Artistic Aesthetics and Semantic Dimensions," by researcher Mohamed Arous, evaluating its scientific value, presenting the critical issues raised, outlining the study's methodology, and assessing its suitability for the selected poetic texts.